Adaptation of Social Mediated Crisis Communication Model: A Systematic Review - Nordalila Nazri; Mohammad Rezal Hamzah; Nor’izah Ahmad (Journal of Human Development and Communication (JoHDeC), 2025)
The social media crisis communication model (SMCC) is a new framework that describes the current landscape and environment for crisis communication. Social mediated crisis communication refers to the dissemination of direct and indirect information on traditional media and social media channels involving various types of users, including influential media, social media followers and social media inactive. Therefore, this article aims to systematically review on adaptation social mediated crisis communication model. This research is based on past research using a systematic survey approach. 4 out of 9 articles were identified for analytical purposes in line with the themes observed; adaptation social mediated crisis communication.